2009
DOI: 10.4278/ajhp.071204127
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Retail Food Environment and Fruit and Vegetable Intake in a Multiethnic Urban Population

Abstract: Purpose To examine relationships between the neighborhood food environment and fruit and vegetable intake in a multiethnic urban population. Design Analysis of cross-sectional survey and observational data. Setting 146 neighborhoods within three large geographic communities of Detroit, Michigan. Subjects Probability sample of 919 African-American, Latino, and White adults. Measures The dependent variable was mean daily fruit and vegetable servings measured using a modified Block 98 food frequency quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
196
4
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(216 citation statements)
references
References 39 publications
4
196
4
12
Order By: Relevance
“…38 Zenk et al 39 found that the presence of a grocery store in the neighborhood was associated with, on average, 0.69 more daily FV servings in the full sample. Availability of fresh FV also seem to be greater in more advantaged areas.…”
Section: Discussionmentioning
confidence: 99%
“…38 Zenk et al 39 found that the presence of a grocery store in the neighborhood was associated with, on average, 0.69 more daily FV servings in the full sample. Availability of fresh FV also seem to be greater in more advantaged areas.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in urban settings of developed countries have reported linkages between food retail and changes in dietary patterns [9,10,26]. Typically, changes in food retail results in increased consumption of energy-dense foods, resulting from greater physical and financial access to highly processed foods.…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic of the urban food environment has also been described as 'food desert', a term used to describe neighborhoods with limited physical and economic access to healthier food options such as fruits, vegetables and other healthy whole foods [6][7][8]. Food deserts, which are often located in poor neighborhoods, are created when supermarkets and other sources of fresh produce are situated, as part of zoning regulations, further away from living areas or require having private transportation to reach [9][10][11]. Because people are increasingly moving to live in urban areas, the relationship between the urban built environment and the food environment has become an important challenge for cities, and more so, when the food environment is linked with dietary behavior and health and nutrition outcomes [12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the evidence available for the USA (6,11,12) , Australia (13) and Europe (8,9) regarding the effects of the local food environment on diet, the field is relatively new in low-or middle-income countries (14)(15)(16)(17) . The unique contribution of our study relies in exploring the role of the urban retail food environment on healthy and unhealthy eating in a rapidly changing, yet understudied, urban and unequal setting in Latin America (18) .…”
mentioning
confidence: 99%